2019
DOI: 10.1111/his.13791
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of CK7 across the spectrum of renal cell carcinomas with clear cells

Abstract: Aims Current available data on cytokeratin 7 (CK7) immunostaining pattern in the clear cell renal cell carcinoma (RCC) spectrum is conflicting. The aim of this study was to assess CK7 immunoreactivity within the spectrum of clear cell renal neoplasms, including clear cell RCC, multicystic renal neoplasm of low malignant potential and clear cell papillary RCC‐like tumours. Methods and results We analysed two clones of CK7 and two tumour blocks for a total of 75 cases divided into five distinct groups: (i) low‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In addition, both chromophobe RCC and clear cell papillary RCC are typically positive for CK7, while conventional ccRCC is usually not, which grants it pivotal importance in the differential diagnosis among clear cell renal neoplasms (36). In 2018, Gonzalez et al suggested that CK7 immunoreactivity in ccRCC is variable and the extent of staining depends on the clinical-histopathological parameters including grade and architectural growth patterns of the tumors (37). Ki-67 is a marker of cellular proliferation and is also involved in ribosomal RNA transcription (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both chromophobe RCC and clear cell papillary RCC are typically positive for CK7, while conventional ccRCC is usually not, which grants it pivotal importance in the differential diagnosis among clear cell renal neoplasms (36). In 2018, Gonzalez et al suggested that CK7 immunoreactivity in ccRCC is variable and the extent of staining depends on the clinical-histopathological parameters including grade and architectural growth patterns of the tumors (37). Ki-67 is a marker of cellular proliferation and is also involved in ribosomal RNA transcription (38).…”
Section: Discussionmentioning
confidence: 99%
“…Among the three types of tissues, the expression of KRT7 was lower in ccRCC cancer tissues and the least in thrombus tissues. An IHC study showed that the extent of KRT7 staining depended on the grade of ccRCC, those with the low-grade ccRCC expressed significantly higher levels of KRT7 than those of the high-grade ones [ 28 ]. This suggests that low KRT7 expression might correlate with a more malignant biological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a few studies claim that VHL variants may not distinguish ccpRCC from ccRCC. For example, a study of 15 tumors found that they are morphologically identical to ccpRCC and that most express CK7; however, molecular profiling indicates that a subgroup of these tumors carries VHL abnormalities [26]. Thus, this group is defined as "clear cell papillary-like RCC" [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of 15 tumors found that they are morphologically identical to ccpRCC and that most express CK7; however, molecular profiling indicates that a subgroup of these tumors carries VHL abnormalities [26]. Thus, this group is defined as "clear cell papillary-like RCC" [26]. Due to the rarity of this kind of renal carcinoma, previous studies did not find variants in common.…”
Section: Discussionmentioning
confidence: 99%